Young adults’ perspectives on chlamydia-related subfertility and a potential predictive subfertility test: A mixed-methods study in the Netherlands - Bernice M. Hoenderboom; Zoïe W. Alexiou; Charlotte M. M. Peters; Karlijn Kampman; Colette van Bokhoven-Rombouts; Christian J. P. A. Hoebe; Birgit H. B. van Benthem (PLoS ONE, 2026)
Background Chlamydia trachomatis (chlamydia) infection control could be more effective if focused on morbidity- rather than prevalence reduction. A predictive test, identifying those at higher risk for chlamydia-subfertility, could be developed to enhance targeted chlamydia control. However, do young adults with a uterus (hereafter “young adults”) want to know their subfertility risk? Methods A sequential mixed methods study was conducted among young adults in the Netherlands to explore perspectives on chlamydia, subfertility, and a potential subfertility test. Five focus groups with Sexual Health Center (SHC) visitors were held to identify potential benefits, barriers, and requirements; results were analysed thematically and used to inform a questionnaire. This questionnaire was distributed online via SHCs and social media. Descriptive statistics and modified Poisson regression were used to assess benefits and barriers of learning one's subfertility risk. Results Nineteen young adults participated in the focus groups, and the resulting themes informed the questionnaire. These included perceived benefits (mental preparation, anticipation, reassurance after a “no increased risk” result), perceived barriers (mental burden of an “increased risk” result, need for blood sampling), and requirements (accuracy, accessibility, follow-up). The questionnaire was completed by 426 participants (median age 22, IQR 20–24). High perceived susceptibility was reported by 11% for chlamydia and 23% for chlamydia‑related subfertility; perceived severity was high for chlamydia and chlamydia-related subfertility, 75% and 88%, respectively. Willingness to use a risk test was 78%. Relief after a “no increased risk” result was expected by 89%, while an increased‑risk result was expected to enhance preparedness (86%) and elicit worry (83%). Additional considerations included motivation for safer sex, negative effects on relationships, and questioning the value of knowing. Conclusion Young adults are concerned about chlamydia‑related subfertility, resulting in high willingness to use a risk test. The expected benefits and barriers should be carefully considered in test development.